Implementasi Kurikulum Merdeka di MAN 1 Kutai Kartanegara: Tantangan, Solusi, dan Prospek Peningkatan - Kadi, Titik (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2024)
This study aims to investigate the implementation of the Merdeka Curriculum at MAN 1 Kutai Kartanegara, focusing on identifying challenges and solutions in planning, implementation, and learning evaluation. The research employed a qualitative case study method with a descriptive approach. Data were collected through in-depth interviews with teachers and school staff, observations, and analysis of curriculum-related documents and learning processes. The findings indicate several challenges in implementing the Merdeka Curriculum, including insufficient understanding of Learning Outcomes (CP) and Learning Objective Paths (ATP), limitations in access to and utilization of technology, and difficulties in implementing effective learning differentiation. Proposed solutions include intensive training for teachers, adequate technology provision, and continuous strengthening of formative assessment. Recommendations for improvement encompass the need for more intensive socialization of the Merdeka Curriculum, enhanced technological infrastructure, development of differentiated learning competencies, and fostering an adaptive and collaborative school culture. This research is expected to contribute to improving the implementation of the Merdeka Curriculum at the upper secondary school level and supporting national educational transformation towards more relevant and adaptive learning in the era of globalization.